C7 WEARABLE CARDIOVERTER – DEFIBRILLATOR IN PATIENTS WITH HIGH RISK OF SUDDEN CARDIAC DEATH: IS IT USEFUL A PATIENT SELECTION?. (18th May 2022) - Bolognesi, M; Rossi, L; Biagi, A; Coccia, M; Sticozzi, C; Comastri, G; Aschieri, D
Abstract: Background: The wearable cardioverter defibrillator (WCD) is considered in patients with increased risk of sudden cardiac death (SDC), in which implanted cardiac defibrillator (ICD) is temporary not definitively indicated. A few registry confirmed efficacy and safety of WCD and left ventricular ejection fraction recovery (LEVS)after wearing time. Methods: We considered in our study 40 consecutively patients that used WCD in Piacenza and Castel San Giovanni Cardiology Department from August 2017 to September 2021 with recent acute myocardial infarction, newly diagnosed cardiomyopathy, primary arrhythmias syndrome awaiting diagnostic completation. They were followed by remore monitoring. The primary outcome were: the need of ICD implantation or not indication to ICD at the of the wearing time, We analyzed clinical variables related to primary outcome. Results: Out of 40 patients, average age 66 years, average LEVS media 29%±12, 5, 88% were males, 32% suffered from diabetes mellitus, 35% renal failure, 55% acute and chronic heart failure, 10% previous ischemic stroke, 17% atrial fibrillation (AF), 12% cardiac arrest (ACC) after STEMI onset, 20% ventricular tachicardia (VT). 27% of these patients took amiodarone, 92% beta blockers and 82% ACEi.The average wearing time of WCD was 51 days and 22, 96 hours dailyAt the end of this period 48% of patients didn't receive ICD implantation for increasing LEVS.We evaluated clinical variables related to primary outcome with Chi Square test and Student's t test.There weren't significant difference regarding primary outcome between ischemic disease and other cardiophaties. The presence of AF, previous stroke, renal failure, hypertension, diabetes mellitus was more but not significant in ICD group. No significant age difference(66.8±14.1 vs 66.3±11.8, p = 0, 6) neither FEVS (29.4±11.6 vs 29.5±12.7, p = 0, 8) was in patients that received ICD versus not received .The clinical variables related to primary outcome only were: ACC after STEMI onset and amiodarone therapy. Conclusions: In our study of patients with WCD, the percentage of LEVS increase is consistent with European registries. A few clinical variables may be related to ICD indication. Further studies can be useful to identify patients who need more of WCD for a lack of LEVS improvement.